PENGARUH GAYA HIDUP TERHADAP MINAT BELI KONSUMEN DALAM BERBELANJA ONLINE (Studi Kasus Pada Mahasiswa STIE BIMA) - Kamaluddin Kamaluddin; Muhajirin Muhajirin (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study aims to determine the effect of lifestyle on buying interest in online shopping at Campus STIE in Bima. This type of research is an associative study. The population in this study is all students who have done online shopping on Campus STIE in Bima. The sample used is 50 people with this technique sampling used in this research is Purposive Sampling. Data analysis technique using simple linear regression test. The results showed that there is a significant influence of lifestyle on buying interest in online shopping is evidenced from t Count of 5.004> 1.676 with a significance value of 0.000 smaller than 0.05 (0.000 <0.05). Keyword: lifestyle and buying interest.